Essays on demand enhancement by food industry participants - Schulz, Lee Leslie (Kansas State University, 2012)
This dissertation empirically examines how demand-enhancing activities conducted by food industry participants affect retail beef steak pricing, consumer demand for ground beef, and industry concentration. It follows the journal article style and includes three self-contained chapters. Chapter 1 uses a two step hedonic model with retail scanner data of consumer beef steak purchases to determine if there are incentives to identify certain attributes and to determine what types of attributes entertain price premiums and at what levels these premiums exists. Results indicate that most branded beef steak products garnered premiums along with organic claim, religious processing claim, and premium steak cuts. Factors influencing brand equity are new brands targeting emerging consumer trends, brands with regional prominence, and those positioned as special-labels, program/breed specific, and store brands. Chapter 2 reports tests of aggregation over elementary ground beef products and estimates composite demand elasticities. Results suggest consumers differentiate ground beef according to lean percentage (70-77%, 78-84%, 85-89%, 90-95%, and 96-100%) and brand type (local/regional, national, store, and unbranded). The range in composite elasticity estimates shows the value of analyzing demand elasticity based on differentiation and not simply considering ground beef as being homogeneous. Composite elasticity estimates provide improved understanding of how consumers make decisions concerning ground beef purchases. Chapter 3 examines industry concentration for the U.S. food manufacturing sector. This study is the first to examine whether particular subsectors within the food manufacturing industry, which operate in the presence of industry-funded check-off programs such as marketing orders, are more or less concentrated than industries without such research and marketing programs. Results provide evidence to support the hypothesis that industries with demand-enhancing check-off programs have lower concentration relative to industries without these programs.
Keywords: Retail beef pricing; Beef demand; Check-off programs; Industry structure; Economics, Agricultural (0503)